HUBUNGAN KEADAAN GIZI DENGAN BEBERAPA ASPEK INTELLEGENSIA - S. Soewondo; B. Abednego; A. Pekerti; D. Karyadi (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1971)
Hubungan keadaan gizi dengan beberapa aspek intelligensi. (The relation of nutritional status on some aspects of intelligence). Presented at the Second National Pediatric Congress. Bandung, 1971. Data obtained in this empirical study agree very well with the theoretical assumption that nutritional status influences the functions of intelligence. The lower the degree of nutritional status, the greater it affects the functions of intelligence. The study showed clearly that undernutrition influences verbal abilities and abstraction. Undernutrition influences also attention and concentration which in turn decrease the mental effectiveness of the subjects; and performance tasks, but which ability is influenced was not clearly shown. It might be due to the environment which was not stimulating for the development of this ability. The effects of undernutrition on perception were also not clearly shown in this study. This study indicated that in the study of nutritional status one should not neglect the influence of the environment. In order that intelligence be able to function at an optimum, any improvement of nutritional status should be accompanied by improvement in socio-economic, psychological and educational conditions.